An Unexpected Complication after Headless Compression Screw Fixation of an Osteochondral Fracture of Patella - Suavi Aydoğmuş; Tahir Mutlu Duymuş; Tolga Keçeci (Case Reports in Orthopedics)
This study evaluated complications associated with implant depth in headless compression screw treatment of an osteochondral fracture associated with a traumatic patellar dislocation in a 21-year-old woman. Computed tomography and X-rays showed one lateral fracture fragment measuring 25 × 16 mm. Osteosynthesis was performed with two headless compression screws. Five months later, the screws were removed because of patella-femoral implant friction. We recommend that the screw heads be embedded to a depth of at least 3 mm below the cartilage surface. Further clinical studies need to examine the variation in cartilage thickness in the fracture fragment.